Properties, geochemical composition, and fertility of highly weathered soils in Central Philippines - Snowie Jane C. Galgo; Victor B. Asio (Eurasian Journal of Soil Science, 2022)
Highly weathered soils are widepsread in the humid tropics. These soils are deep, clayey, and reddish and contain scant amounts of nutrients like Si due to excessive leaching, heavy desilication-aluminization, and erosion owing to their slope gradient and position. However, few investigations have been published in terms of their nature, characteristics, and nutrient status, especially for the geologically young Philippine islands. This study assessed the properties, geochemical composition, and fertility of deep and highly weathered soils developed from various parent materials in Central Philippines (Leyte and Samar). Sampling covered the entire soil profiles, including the lower portions, that are usually neglected in common soil characterization studies. Among the soil profiles, only profiles 3 and 8 have developed from non-uniform or heterogeneous parent materials. Findings likewise revealed heavy losses of K2O, CaO, MgO, and Na2O from the highly soil profiles evaluated. The amount and profile distribution of K2O and CaO is below 0.5% in the entire profile of most soils. On the other hand, there is apparent enrichment of Al2O3, Fe2O3, and to a lesser extent SiO2 in the highly weathered soil profiles, thus supporting the residua hypothesis. In terms of morpho-physical characteristics, the soils have deep solum, reddish color, subangular structure, friable moist consistence, and sticky and plastic wet consistence which are all related to the highly weathered nature of the soils. They also generally have low bulk density and higher porosity due to the iron oxides aggregation effect. The strong acidity (pH <5) and negative delta pH values revealed that the soil colloids possess a negative net charge. Nutrient status also showed low contents of organic matter, total N, available P, and exchangeable bases. Majority of the deep and highly weathered soils evaluated have possibly developed from homogenous parent materials. The soils are classified as Hapludox, Hapludult, and Paleudult.